The Trinity in Christian-Muslim Conversation - Swanson, Mark N. (Dialog, 2005)
Christians need to recognize more fully the force of Muslim arguments on behalf of the oneness of God against the doctrine of the Trinity. Christians could benefit from the Islamic concept of shirk, proscribing the association of something that is not God in the honor and respect due to God alone. Christian trinitarian theology may be improved thereby; and certainly Christian-Muslim conversation will be enriched.